Beach Users' Perceptions of Coastal Regeneration Projects as An Adaptation Strategy in The Western Mediterranean. (March 2022) - Sauer, Inga; Roca, Elisabet; Villares, Míriam
Some coastal environments facing climate change risks are starting to be managed with nature-based solutions (NBS). Strategies based on the rehabilitation of green infrastructures in coastal municipalities, such as renaturalization of seafronts, are considered adaptive to the effects of climate change but may cause misconceptions that could lead to social conflicts between the tourist sector and the society. A survey was carried out to study user perceptions on the effects of climate change, preferences for adaptation strategies, and the assessment of projects of dune reconstruction. We find that while beach users recognize the benefits of NBS for environmental conservation and storm protection, they show little concern about possible effects of climate change on recreational activity and have limited understanding about the protective capacity of NBS. Thus, a greater effort must be made to better explain the effects of climate change and the potential benefits of NBS in coastal risk management.